2020
DOI: 10.3390/su12083321
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Type of Information Categorization in Online Curation Service Depending on Psychological Ownership

Abstract: With the development of the Internet, consumers can acquire a variety of information; however, as the amount of information continuously increases, it becomes difficult for consumers to make decisions. In this era of information overload, online curation services are emerging to help consumers choose the information they want. In these online services, information is grouped and classified according to certain criteria and presented to consumers. In this context, there are typical goal-derived and taxonomic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The theoretical contributions of this study are as follows. The results of this study once again corroborated the broad findings of preceding research, namely that psychological ownership can develop even for online services, which are intangible targets [16,21,22]. As digitization progresses, the targets individuals own are becoming more and more intangible.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The theoretical contributions of this study are as follows. The results of this study once again corroborated the broad findings of preceding research, namely that psychological ownership can develop even for online services, which are intangible targets [16,21,22]. As digitization progresses, the targets individuals own are becoming more and more intangible.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, recent studies have investigated the role of psychological ownership in the digital world and verified that users experience psychological ownership of intangible targets such as online services and contents [11,[16][17][18][19]. Furthermore, recent studies have suggested that users' decisionmaking can vary depending on the degree of psychological ownership of online services, drawing attention to the role of psychological ownership in the online context [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The first is the expansion dimension of the variable. This study does not take into account individual propensity or ability, and if this part such as construal level [55], psychological ownership [56][57][58], knowledge level [59] or consumer profile [60] is added, much more sophisticated insights can be derived. The second is the diversification dimension of the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is necessary to consider regulatory focus and construal level, which are informational variables that consumers continuously process and are currently being studied by scholars [35][36][37][38][39][40][41][42][43][44][45]. Additionally, depending on product characteristics (tangible vs. intangible, actual vs. virtual), the effects of ECI and CCI can be different [40][41][42]. Finally, it is possible to verify whether the results of this study are viewed as real data in real situations through studies supported by larger data [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%